Die Verdopplung des Verbs laa 'lassen' im Zürichdeutschen - Schlatter Gappisch, Katja (Linguistik Online, 2011)
In some Swiss German dialects the verb laa 'let' can be doubled under certain conditions. The paper discusses the factors accounting for this variation. It investigates the syntactic environment of laa-constructions in the dialect of Zurich. The analysis of the data suggests that, first, the laa-doubling is favoured in certain constructions such as, for instance, imperative constructions. Second, the elder informants use the laa-doubling more often than the younger ones.